Fatty Acid Composition and Effect of Repeated Use on the Quality of Traditional Mandar Cooking Oil - Fauziah Fauziah; Diesna Sari; Rahmaniah Rahmaniah; Dewi Rahmayani (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Traditional coconut oil of mandar is oil extracted from coconut flesh through a heating process. Repeated use of cooking oil has the potential to reduce the oil’s quality, characterized by an increase in free fatty acid levels. The study aimed to analyze the fatty acid composition and the effect of repeated use on the quality of traditional coconut oil from mandar. This study was an experimental design with a completely randomized design (CRD). The frying technique used was deep fat frying with a total of 9 liters of oil. The product being fried was kepok banana, with a total weight of 9 kg, fried at 180°C for 10 minutes in each cycle. There was a 5-minute interval between frying cycles, and a total of 9 cycles were performed on the same day. The parameters analyzed in this research were free fatty acid content and fatty acid profile of traditional coconut oil of Mandar. The results showed that the fatty acid profile was dominated by saturated fatty acids (76,49%) and a small portion of unsaturated fatty acids (0,59%). The level of ALB in traditional coconut oil of mandar did not exhibit significant differences (p>0,05) from the initial use up to the 9th repetition. Thus, traditional coconut oil from Mandar remains suitable for frying purposes for up to 9 cycles.